Paradigm of educational modernization Nurcholish Madjid perspective and relevance to the merdeka belajar concept - Abdurrohim; Sholeh, Mohammad; Zakki Fuad, Ahmad; Zaini, Achmad (UIN Salatiga, 2024)
The aim of this research is to analyze the development of Islamic education through the newly launched concept of